2013
DOI: 10.1007/s10554-013-0346-z
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial booster-pump function as a predictive parameter for new-onset postoperative atrial fibrillation in patients with severe aortic stenosis

Abstract: Postoperative atrial fibrillation (POAF) is associated with increased risk of embolic events and heart failure, but its associated factors remains unknown. Left atrial (LA) subclinical mechanical dysfunction caused by the acute stress of surgery may be clinically manifested as POAF. The purpose of our study was therefore to test the hypothesis that preoperative LA subclinical myocardial dysfunction is a potential predictor of development of POAF in patients with aortic stenosis (AS). We studied 27 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Additionally, increased LA volume has been introduced as an independent predictor of prognosis in these patients [18]. However, the role of atrial function as a contributor to the patients' outcomes has been poorly investigated to date [32]. With the present study, we sought to attain a deeper insight into the risk stratification of asymptomatic AS patients by investigating whether atrial function impairment could actually have any role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, increased LA volume has been introduced as an independent predictor of prognosis in these patients [18]. However, the role of atrial function as a contributor to the patients' outcomes has been poorly investigated to date [32]. With the present study, we sought to attain a deeper insight into the risk stratification of asymptomatic AS patients by investigating whether atrial function impairment could actually have any role.…”
Section: Discussionmentioning
confidence: 99%
“…It is demonstrated that after transcatheter aortic valve implantation or surgical aortic valve replacement, a significant anatomical and functional reverse remodeling of both LV and LA has been detected in terms of reduced LV mass and improved LV and LA longitudinal performance [39][40][41][42]. Moreover, a reduced LA strain has already been associated with the severity of AS and has been identified as a predictor of atrial fibrillation recurrence after aortic valve replacement [32].…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic importance of LA pump function in HFpEF is not well known. LA pump function is associated with risk of AF in patients with aortic stenosis 40 and in the general population, 41 but has also been associated with adverse cardiovascular events in hypertensive populations. 42,43 Impaired LA contractile reserve secondary to progressive elevation of LV filling pressure may contribute to HFpEF symptoms, particularly during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Galli et al involving 128 patients with severe AS, reduced LA systolic strain was associated with an increase in all-cause mortality, worsening HF and cardiac hospitalization (89). LA systolic strain was also a predictor of postoperative AF in patients with severe AS undergoing surgery (90).…”
Section: Valvular Heart Diseasementioning
confidence: 99%